Polish-Ukrainian relations in Galicia during the process of parcellation of landowners' estates in 1867-1914 - Mykola Vitenko (Cхід, 2013)
The article investigates the process of fragmentation of the landowners' estates in Galicia in 1867 - 1914, the attempts of Polish political parties and economic organizations to limit access of Ukrainian farmers to purchasing the lands of the bankrupt gentry, the resettlement of Polish colonists to the Ukrainian ethnic lands and the influence of the Polish colonization of Eastern Galicia on the Polish-Ukrainian relations.